The Effect Of Innovation, Tqm Implementation And Entrepreneurship Orientation On Competitive Advantage Strategies In Building Msme Performance - Akbar Pahlevi; Rahab Rahab (Green Publisher Indonesia, 2022)
The number of MSMEs engaged in timber requires companies to determine strategies that can make MSMEs seek and retain consumers. A model of MSME business continuity has been developed by placing the dependent variable on company performance as a proxy for MSME business continuity. In this model there are three antecedents of business continuity which include innovation, entrepreneurial orientation and TQM